2008
DOI: 10.1136/jmg.2008.063693
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in LAMB2 causing a severe form of synaptic congenital myasthenic syndrome

Abstract: Background: We describe a severe form of congenital myasthenic syndrome (CMS) associated with congenital nephrosis and ocular malformations caused by two truncating mutations in the gene encoding the laminin β2 subunit ( LAMB2 ). Methods and results: Mutational analysis in the affected patient, who has a history of a serious untoward reaction to treatment with acetylcholinesterase inhibition, revealed two frame-shifting heteroallelic mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
115
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 26 publications
8
115
0
Order By: Relevance
“…The kinetic mutations fall into two categories according to whether they induce slow or fast channel syndromes [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] .…”
Section: Defects In Acetylcholine Receptor Subunitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic mutations fall into two categories according to whether they induce slow or fast channel syndromes [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] .…”
Section: Defects In Acetylcholine Receptor Subunitsmentioning
confidence: 99%
“…[4][5] To date 13 genes have been found to cause CMS when mutated. These are the pre-synaptic acetyltransferase CHAT 6 , the gene COLQ 7-8-9 encoding the triple stranded collagenic tail of the synaptic acetylcholinesterase (AChE), the genes encoding the different subunits of the postsynaptic acetylcholine receptors (AChR) CHRNA1, CHRNB1, CHRND, CHRNE and CHRNG, the RAPSN gene encoding the postsynaptic protein rapsyn 10 , the postsynaptic muscle specific kinase (MUSK) gene 11 , the postsynaptic sodium channel (SCN4) 12 , the DOK7 gene encoding the postsynaptic Dok-7 protein [13][14] , the LAMB2 encoding the synaptic Laminin B2 protein 15 , the AGRN gene encoding the postsynaptic agrin protein 16 and the PLEC1 gene encoding the postsynaptic protein plectin. 17-18-19 Genetic classification of the different CMS cohorts reveals that the majority of CMS patients have mutations in genes expressing postsynaptic endplate proteins [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] (table 1).…”
Section: Introductionmentioning
confidence: 99%
“…No fewer than 11 defective molecules at the NMJ have been identified to date. The mutant molecules include (i) acetylcholine receptor (AChR) subunits that forms nicotinic AChR and generate endplate potentials Sine et al, 1995), (ii) rapsyn that anchors and clusters AChRs at the endplate Milone et al, 2009), (iii) agrin that is released from nerve terminal and induces AChR clustering by stimulating the downstream LRP4/MuSK/Dok-7/rapsyn/AChR pathway (Huze et al, 2009), (iv) muscle-specific receptor tyrosine kinase (MuSK) that transmits the AChR-clustering signal from agrin/LRP4 to Dok-7/rapsyn/AChR (Chevessier et al, 2004;Chevessier et al, 2008), (v) Dok-7 that interacts with MuSK and exerts the AChR-clustering activity Hamuro et al, 2008), (vi) plectin that is an intermediate filament-associate protein concentrated at sites of mechanical stress (Banwell et al, 1999;Selcen et al, 2011), (vii) glutamine-fructose-6-phosphate aminotransferase 1 encoded by GFPT1, the function of which at the NMJ has not been elucidated (Senderek et al, 2011), (viii) skeletal muscle sodium channel type 1.4 (Na V 1.4) that spreads depolarization potential from endplate throughout muscle fibers , (ix) collagen Q that anchors acetylcholinesterase (AChE) to the synaptic basal lamina Kimbell et al, 2004), (x) 2-laminin that forms a cruciform heterotrimeric lamins-221, -421, and -521 and links extracellular matrix molecules to the -dystroglycan at the NMJ (Maselli et al, 2009), (xi) choline acetyltransferase (ChAT) that resynthesizes acetylcholine from recycled choline at the nerve terminal (Ohno et al, 2001). AChR (Lang & Vincent, 2009), MuSK (Hoch et al, 2001;Cole et al, 2008), and LRP4 (Higuchi et al, 2011) are also targets of myasthenia gravis, in which autoantibody against each molecule impairs the neuromuscular transmission.…”
Section: Introductionmentioning
confidence: 99%
“…These defects include invasion of Schwann cell in the synaptic space and structural defects leading to muscle weakness and fatigability (Maselli et al 2009), symptoms also observed in Lamb2 -/-mice (Patton et al 1998). The mice also exhibit congenital nephrosis (Noakes et al 1995b), retinal defects (Libby et al 1999) and failure to thrive.…”
Section: Lamb2 Gene Mutations Pierson Syndrome and The Gbm As Filtramentioning
confidence: 99%
“…Due to better management of renal problems, Pierson syndrome patients' life expectancy has increased and led to the manifestation of a neuromuscular phenotype in some individuals (Maselli et al 2009;Wuhl et al 2007). These defects include invasion of Schwann cell in the synaptic space and structural defects leading to muscle weakness and fatigability (Maselli et al 2009), symptoms also observed in Lamb2 -/-mice (Patton et al 1998).…”
Section: Lamb2 Gene Mutations Pierson Syndrome and The Gbm As Filtramentioning
confidence: 99%